(untitled) (Dissertation Nursing, 2025)
BACKGROUND: Managing an oncology palliative care pathway is often burdensome for professionals. PURPOSE: To evaluate the feasibility of implementing a dedicated nursing case management service to improve time management and task satisfaction among healthcare providers and administrative staff in an outpatient palliative care setting. METHODS: A pre-post survey study was conducted from February to August 2023. All professionals in an outpatient palliative care clinic estimated daily time spent on each activity and their task satisfaction before and six months after implementing a nursing case management service. Data on collection procedures, clarity of instructions, measure relevance, adequacy, and intervention implementation were also gathered. RESULTS: Eleven professionals participated in the study. All feasibility measures were considered appropriate by responders. After case management implementation, palliative care physicians reported less time spent on treatment plan setup (-7.00 min/day), phone calls (-27.8 min/day), and completing reports and administrative records (-13.7 min/day). Nursing anamnesis (-10.0 min/day) and care coordination and organization (-15.8 min/day) showed a reduction in time between T0 and T1, and satisfaction about the latter varied from 3 to 5.5 points. CONCLUSIONS: The proposed study design was considered feasible and adequate by all responders. The introduction of a nurse case manager led to a reduction in telephone calls and administrative documentation for medical staff, and increased job satisfaction. Bigger and more robust studies are needed to investigate the impact of a nurse case manager on satisfaction and time management of professionals in Palliative Cancer Care.